Colposcopic evaluation of cervix with abnormal papsmear findings: prospective analytical study at our tertiary care centre - Verma, Bhawna; Rastogi, Radha; Srivastava, Dipti; Saharan, Saroj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pap test has been successful in reducing the incidence of cervical cancer by 80% and mortality by 70%. Any women with a cytologic specimen suggesting the presence of HSIL on Pap smear should undergo colposcopy and dissected biopsy. Prevention of invasive cancer by early detection and treatment of cervical intraepithelial neoplasia (CIN) currently offers the most cost effective, long term strategy for cervical cancer control. The aim of study was to minimise disagreements and make colposcopy assessment quick, accurate and easy for follow-up. Methods: Prospective analytical study of 300 gynaecological patients with abdominal Pap smear findings between June 2020 to Dec 2020 at R.N.T. Medical College, Udaipur. All of them were subjected to colposcopy and dissected biopsy from the abdominal areas. The incidence of CIN/invasive carcinoma was calculated by proportion/percentage. Results: Incidence of invasive carcinoma was <1% but the incidence of premalignant lesion CIN was high (20.9%), CIN 2/3 and CIS were present in 6.9%. Conclusions: Patients with persistent inflammation pap smear can harbour high proportion of CIN and hence these patients need further evaluation through colposcopy.